2006
DOI: 10.1590/s0100-204x2006000500010
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and environment interaction on soybean yield in Mato Grosso State, Brazil

Abstract: -The objective of this work was to investigate the genotype-environment interaction in Mato Grosso State, MT. The relative importance of locations, years, sowing dates and cultivars and their interactions was analyzed from data collected in regional yield trials performed in a randomized complete block design with four replications, from 1994-1995 through 1999-2000, in Locations are relatively more important than years for yield testing soybeans in the MT State, therefore, investment should be made in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(1 reference statement)
0
4
0
1
Order By: Relevance
“…The result of the current study revealed that the tested genotypes, in the designated locations and stipulated years, are quite divergent (Table 1). The two way interactions between genotypes and locations and genotypes and years are all not significant indicating the possibility of selection for wider adaptation from the tested genotypes (Toledo et al ., 2006). Location × year interaction effects were significant at various level of significance of all traits except DM (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The result of the current study revealed that the tested genotypes, in the designated locations and stipulated years, are quite divergent (Table 1). The two way interactions between genotypes and locations and genotypes and years are all not significant indicating the possibility of selection for wider adaptation from the tested genotypes (Toledo et al ., 2006). Location × year interaction effects were significant at various level of significance of all traits except DM (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The cultivars with determinate growth habit that were better adapted for the South Region of Brazil until 2000 had a maturity ranging between 120 and 125 d (Specht et al., 2014; Toledo et al., 2006). After 2000 there was a need to obtain earlier cultivars, which allowed double cropping of soybean with corn ( Zea mays ) or cotton ( Gossypium hirsutum L.) in a single season, and which favored the control of Asian soybean rust ( Phakopsora pachyrhizi ) that was emerging in Brazil (Specht et al., 2014; Toledo et al., 2006). However, determinate‐type cultivars that matured in less than 115 to 120 d presented low yield potential, as they needed a minimum period of time before flowering to reach an adequate development (Specht et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that, although the set of cultivars evaluated in this study did not show significant changes in DM over the years, the number of early cultivars released in the Midwest Region has increased over the last few years, as observed for the South Region in the present study. In the Midwest Region, there was also a need to use early cultivars that allowed double cropping with corn or cotton in the same season, in addition to favoring the control of Asian soybean rust (Specht et al., 2014; Toledo et al., 2006). The introduction of indeterminate growth‐habit germplasm in Midwest Region also showed yield potential combined with earliness, which until then were difficult to obtain with determinate growth‐habit cultivars (Specht et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the difficulty of recommending cultivars as a function of the genotype x environment interaction, it is necessary to perform tests on a larger number of sites (Carvalho et al, 2002;Toledo et al, 2006). In the state of Goiás, for example, there is a wide variability of growing conditions.…”
Section: Introductionmentioning
confidence: 99%